1999
DOI: 10.1258/0956462991914050
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Trachomatis Infection in Women with and without Cervical Intraepithelial Neoplasia

Abstract: The aim of the study was to compare the frequency of Chlamydia trachomatis infection in patients with cervical intraepithelial neoplasia (CIN) and in women without cervical pathology. In a study group of 423 patients with histologically proven CIN and in 108 controls with normal cervical smear, cytological material for direct immunofluorescence analysis was obtained. Among 423 patients, 24 (5.7%) had CIN 1, 108 (25.5%) CIN 2 and 291 (68.8%) CIN 3. Among all patients with CIN, 27 (6.4%) were C. trachomatis posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…A similar study done in Brazil 36 also showed a significantly high prevalence of C. trachomatis among women with histologically diagnosed precancerous lesion of the cervix. However, a study in Slovenia 33 and Netherlands 34 did not find any significant association. The similarities observed in our study and that of the Argentina and Brazil studies may be due to the relatively high prevalence of sexually transmitted infection often reported in developing countries as opposed to the developed countries.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A similar study done in Brazil 36 also showed a significantly high prevalence of C. trachomatis among women with histologically diagnosed precancerous lesion of the cervix. However, a study in Slovenia 33 and Netherlands 34 did not find any significant association. The similarities observed in our study and that of the Argentina and Brazil studies may be due to the relatively high prevalence of sexually transmitted infection often reported in developing countries as opposed to the developed countries.…”
Section: Discussionmentioning
confidence: 82%
“…The role of Chlamydia trachomatis in the pathogenesis of CIN remains unexplained and sometimes controversial; while some studies show no significant association between C. trachomatis and cytologically or histologically diagnosed precancerous lesion of the cervix, 33,34 others have shown a significant association. 35,36 In this study, a higher prevalence of C. trachomatis (50%) was reported among women with abnormal smear compared to women with normal cytology (16.7%) and this difference was statistically significant (OR = 10.95; P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, in an older study dating from 1999, it was concluded that Chlamydia trachomatis seems not to interfere with the development of CIN. 33 In an article published in 2008, no statistical effect of Chlamydia trachomatis infection was reported of progression, regression, and persistence of CIN. 34 This study provides an oversight of HSIL and the full range of cervical infections as detected by cytology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CT infection is more frequent in females with CIN than in females with normal cytological fi ndings (5). However, Takac et al (6) indicate that CT infection is not related to the development or even to promotion of CIN. CT infections can cause several complications such as pelvic infl ammatory disease (PID) and infertility (7,2).…”
mentioning
confidence: 99%